Hemostatic efficiency of modern topical sealants: comparative evaluation after liver resection and splenic laceration in a swine model - Fonouni, Hamidreza; Kashfi, Arash; Majlesara, Ali; Konstantinidis, Lukas; Soleymanzadeh Gharabaghi, Negin; Kraus, Thomas W.; Mehrabi, Arianeb; Oweira, Hani (Journal of biomedical materials research. Part B, Applied biomaterials, 2017)
Abstract Parenchymal transection during hepatobiliary surgery can disrupt small vasculature or bile ducts, which could be managed difficultly. Sealants are helpful tools to achieve better hemostasis. The aim of this study is to analyze the hemostatic efficiency of four modern sealants in a porcine model. In this study, 40 landrace pigs were assigned equally to the control (without sealant) and four sealant groups. Standardized liver resection and splenic lesions were performed and left without using sealant (control) or treated with one of the following sealants: TachoSil?, Tissucol Duo?, Coseal?, and FloSeal?. We measured relative and absolute bleeding times (seconds) as well as total blood loss (g) in a maximum observation time of 300 s. Sealants could show a significantly improved hemostasis comparing to the control group. However, hemostasis was heterogeneous among the sealant groups (liver resection: 60%?100%, spleen injury: 70%?100%). The mean blood loss decreased significantly using sealants comparing to control group (liver resection: 6?120 fold, spleen injury: 2.5?36 fold). The hemostatic time in groups that achieved complete hemostasis was different in each sealant group (liver resection: 30?166 s, spleen injury: 60?180 s). We conclude that the hemostatic efficacy of modern sealants is impressive but heterogeneous in liver resection or splenic lesion. To maximize the effectiveness of these tools, the indication of each sealant should be carefully considered in individual settings by the surgeons. ? 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1307?1316, 2018.
Gesehen am 11.04.2018